SIMPLIFICATION IN PHONOLOGICAL ACQUISITION (A CASE STUDY OF ATALA) - Evi Jovita Putri; Zakia Rachmah (Universitas Nasional, 2021)
This study aims to determine a child’s language acquisition at the phonological level and to describe its simplification of sounds. This research is a case study applying a qualitative descriptive approach. The subject observed is Atala, a boy aged 28 months. The data are obtained by recording and direct observation approximately one month. The data are transcribed and then identified by comparing the child's pronunciation with adult mode in order to see the simplification of the sounds in the child's speech. Based on the Ingram’s theory, 34 data presented shows the simplifications of sounds occur in the form of substitution consisting of stopping (6), fronting (9), and gliding (5); assimilation containing consonant harmony (3) and vowel harmony (2); while syllable structure consisting of last consonant reduction (2) and initial onset reduction (7). It is found that the simplifications of sounds commonly happen on the substitution covering fronting and stopping then syllable structure covering initial onset reduction. It is due to an indication that the child is imperfect to actively move the articulators in appropriate place or manner of articulation especially in producing some fairly complex sounds. There are some sounds cannot be produced in this case, such as sounds [r], [s], and [g], the subject obviously simplifies these sounds when he has to pronounce them in any positions of a word. Meanwhile he has been able to produce singly vowels and consonant [a], [i], [u], [e], [o], [p], [b], [t], [d], [m], [n], [ɲ], [ŋ], [w], [y], [j], [c], [l], [h], [?], but sometimes simplifies them in certain position of the word.